Internet of things in business transformation : developing an engineering and business strategy for industry 5.0 - Gandhi, Parul (John Wiley & Sons, Inc., 2021)
"IoT is to provide better services to the users, thereby, improving the quality of life, and the idea of integrating IoT with other emerging technologies like AI, blockchains and cloud computing can lead to the development of systems that are more robust, intelligent, secure and powerful. IoT and its applications in the fields of healthcare, smart homes, agriculture, robotics, and industries. Technological advancements continue to grow at an incredible speed so that Industry 5.0 which will be increased collaboration between humans and smart systems with the highspeed accuracy of industrial automation. The benefits will be extended to utilities and grid operators in secured ecosystem as they will be able to balance supply and demand in real-time as it also supports renewable energy integration into the grid in a fruitful way"--